BLUMENTHAL SCREENING FOR CARDIOVASCULAR RISK IN ASYMPTOMATIC PATIENTS - J. S. Berger; C. O. Jordan; D. Lloyd-Jones; R.S. Blumenthal (Рациональная фармакотерапия в кардиологии)
Blumenthal screening for cardiovascular risk in asymptomatic patients.